Progressive failure analysis of soil slopes considering the influences of humidity and loading - Fang, Juan; Luo, Aizhong; Shao, Shengjun; Chen, Changlu (Frontiers in Ecology and Evolution, 2023)
To analyze the progressive failure of structural loess slopes due to changes in humidity and loading, this study analyzes the degrees of influence of these changes on slope failure and their relationships with various structural parameters. According to the analysis, the shear failure of the soil gradually develops with the change of the water content. When the water content reaches a 17%, with the development of shear deformation, the shear zone is formed and finally penetrates the soil body. With the increase of the water content, the total displacement of the slope body gradually develops. When the water content reaches 17%, the total displacement of the slope body changes suddenly. This mutation is consistent with the formation of the shear zone. The sudden change of displacement indicates the penetration of the shear zone and the damage and slippage of the slope. With the increase of the soil moisture of the slope, the strain localization phenomenon occurs, the development of strain localization and shear bands increases, the structural damage increases, and the quantitative structural parameters decrease. The quantitative parameters can therefore be used to evaluate the feasibility and rationality of the progressive failure process of homogeneous structural loess slopes.